GROUNDWATER AND LAKE EVOLUTION IN THE BADAIN JARAN DESERT ECOSYSTEM, INNER MONGOLIA - Ma J.; Edmunds W.M. (My University, 2006)
The amount and timing of aquifer recharge and the evolution of lakes and groundwater in the south-eastern Badain Jaran desert of Inner Mongolia, with high megadunes, has been investigated using stable isotopes and hydrochemistry. Unsaturated zone moisture profiles down to 22 m have recorded recharge over 1185 years. Small but finite amounts of recharge are recorded with mean recharge rates of 0.95-1.33 mm year−1, determined using a chloride mass balance technique. The unsaturated profile also acts as a unique archive of hydrological and climate change. Before 1300, it was relatively dry but distinct wet periods may be recognised during 1340-1450, 1500-1610 and 1710-1820. Since the mid 1800s, the climate shows a trend towards greater aridity. The interdune lakes are generally fresh but locally, hypersaline lakes are found in juxtaposition. This implies that in general, the lakes have low residence times and flow back into the dune system, but sedimentary obstruction locally prevents outflow and extreme evaporation occurs. The stable isotope records show that the lakes are fed by palaeowaters which on the basis of other proxy data must predate the Last Glacial Maximum. Their recharge source is problematic but most likely this derives from a diminishing water table extending some 30 m south to the Yabulai Mountains.
Keywords: HYDROCHEMISTRY; GROUNDWATER RECHARGE; PALEOHYDROLOGY; UNSATURATED ZONE; BADAIN JARAN DESERT